Dimensions of a cultural policy - Lal,Sheo Kumar (Delhi, 1982)
Dimensions of a Cultural Policy is an in-depth analysis of the range that a difficult and challenging subject offers. The book, not only examines the possibility and necessity for having a cultural policy for a country like ours but also presents the analysis of the socio economic conditions of the country in the context of which such a policy should be considered. The book will be of interest not only to those who are specialist in the subjects like Sociology, Anthropology, History, Philosophy and Literature but also to general readers.
Keywords: India Culture